Revitalizing Endangered Languages A Practical Guide - Olko, Justyna; Sallabank, Julia (Humanities, 2021)
Written by leading international scholars and activists with a wealth of practical experience, this guidebook provides ideas and strategies to support effective language revitalization. It is written in a clear, accessible style, making it suitable for non-specialists, as well as researchers and students interested in language revitalization.